Reforming Gift-Giving Traditions to Promote Women's Inheritance in Pakistan: Legal and Islamic Insights (Al-Qamar, 2024)
Women’s right to inheritance is established and protected by Islam.Pakistan, as an Islamic country, expects its citizens to obey all of theprinciples enshrined in the Holy Quran and Sunnah. However, incase of inheritance to women, people often deviate from theseguidelines. Although many efforts are in progress to augment thesocial and economic status of women in this country, despite thatmalafide practice persists in this society where Pakistani women,before or at the time of marriage, are compelled, due to undueinfluence, to surrender their inheritance in favor of their brothers.This systemic exclusion of women from inheritance happens throughthe transfer of property using the guise of gift. Even though courts inthe country are cognizant of this practice and are actively trying totackle it through their judgments, yet their efforts alone areinsufficient. In these circumstances, what this society needs areamendments in both criminal and civil laws to unambiguouslyprohibit the deprivation of women from their rightful inheritance.Additionally, it is also the legal as well as moral duty of every
Keywords: Inheritance; Women empowerment; Gift of Property; Women’s Right to Inheritance in Islam; Women’s Right to Inheritance in Pakistan